CHAPTER 6 Development of SOFC Interconnect Stainless Steels - Sbastien Chevalier; Lionel Combemale; Ioana Popa; Somrerk Chandra-ambhorn; Walairat Chandra-ambhorn; Piyorose Promdirek; Patthranit Wongpromrat (My University, 2020)
The chapter introduces components and working principle of solid oxide fuel cells (SOFCs). It is followed by the explanation on the choices of materials focussing on ferritic stainless steels. The review is further made on the required properties of these steels, i.e. low oxidation rate, low chromium species volatilisation rate, high electrical conductivity and good scale adhesion. For the oxidation aspect, the behaviour of stainless steel interconnect in cathode, anode (hydrogen and biogas), and dual atmospheres are described. Surface modification by pre-oxidation and coatings to improve the oxide electrical conductivity and to reduce chromium species volatilisation is finally reviewed.
Keywords: Volatilisation; Advancements in Solid Oxide Fuel Cells